2014
DOI: 10.2179/14-034
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Controls of Reproduction and Early Growth ofLindera melissifolia(Lauraceae)

Abstract: Lindera melissifolia is a federally endangered endemic shrub of the southeastern United States. Numerous populations are gender-biased. The goal of this study was to determine environmental conditions most appropriate for establishment and growth of seedlings and adult females. Seedlings were grown under varied moisture and light to compare growth rates and morphological ratios. Seedlings were clipped to simulate two levels of disturbance, and their shoot sprouting ability was assessed. Densities of adult flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
2
1
0
Order By: Relevance
“…In concurrence with our expectation, L. melissifolia shrubs acclimated to the low-light environment produced the least amount of biomass-this is consistent with the concept that with all other factors being equal, light is the primary limitation to plant growth (Luken et al 1997, Gardiner and Hodges 1998, Poorter et al 2012. Unks et al (2014) projected that low-light availability would limit biomass accumulation in this species during the first year of seedling growth, and our results extend this conclusion through the third growing season at the FRF. In addition to limiting whole-plant biomass accumulation, the stress of low-light availability appeared to trigger a plastic response in photosynthate allocation among tissues.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In concurrence with our expectation, L. melissifolia shrubs acclimated to the low-light environment produced the least amount of biomass-this is consistent with the concept that with all other factors being equal, light is the primary limitation to plant growth (Luken et al 1997, Gardiner and Hodges 1998, Poorter et al 2012. Unks et al (2014) projected that low-light availability would limit biomass accumulation in this species during the first year of seedling growth, and our results extend this conclusion through the third growing season at the FRF. In addition to limiting whole-plant biomass accumulation, the stress of low-light availability appeared to trigger a plastic response in photosynthate allocation among tissues.…”
Section: Discussionsupporting
confidence: 92%
“…As we hypothesized, L. melissifolia raised under low light favored biomass accumulation in leaf and stem tissues over biomass accumulation in root tissue. Others have reported a corresponding shift in proportional biomass accumulation by seedlings (<1 year old) of this species (Unks et al 2014), but it is noteworthy that this response was confirmed in our study of plants with more advanced ontogeny. The plastic shift in photosynthate allocation to aboveground tissues is a strategy to increase light capture in low-light environments (Walters et al 1993).…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, Unks et al. ( 2014 ), who studied L. melissifolia at 2 field sites in North Carolina, USA, were unable to establish a correlation between light transmittance through the overstory and the number of flowering stems in colonies. Our results demonstrate the strong effect of light availability on intensity of sexual reproduction in L. melissifolia .…”
Section: Discussionmentioning
confidence: 92%